Analisis dan Implementasi Proses Quality Assurance pada Pengembangan Aplikasi Point of Sale di PT. Olsera Indonesia Pratama - Ferdynand Kee; Nimatul Ma'muriyah; Andik Yulianto (National Conference for Community Service Project (NaCosPro), 2025)
This practical work activity focuses on the analysis and implementation of the Quality Assurance (QA) process in the development of a Point of Sale (POS) application at PT. Olsera Indonesia Pratama. The main objective of this activity is to apply a systematic testing process to ensure software quality and stability before its release to end-users. The implementation method adopts the Agile workflow applied within the company, utilizing a hybrid testing approach that combines manual testing for complex features and basic automation testing for efficiency. The testing process used the Black Box Testing method on various features across multiple platforms, including mobile and web applications. The results of the implementation show that a structured QA process successfully identified various functional and non-functional issues, validated bug fixes effectively, and ensured that key features like "redeem voucher" and "price tiers" function reliably and consistently. This activity concludes that a fully integrated QA role within the development cycle is crucial for maintaining product quality in a fast-paced technology industry environment.